Engineering Disordered Many‐Particle Plasmonic Nanoclusters for Wafer‐Scale Uniform and Giant Electromagnetic Field Enhancement - Kim, Minjun; Devaraj, Vasanthan; Seo, Hyeon‐Seok; Eom, Seong‐Jae; Lee, Jeong‐Su; Lee, Donghan; Jeon, Min Yong; Zentgraf, Thomas; Lee, Jong‐Min (Laser & Photonics Reviews)
Scalable plasmonic technologies face a critical trade‐off: few‐body architectures offer high enhancement but are sensitive to fabrication flaws, while scalable methods like solid‐state dewetting yield large, low‐enhancement gaps. We introduce a paradigm shift using a many‐body plasmonic architecture inspired by statistical mechanics. By moving toward the continuum limit, local geometric variations are statistically averaged out, effectively decoupling optical performance from microscopic disorder. We implement this concept via a lithography‐ and etching‐free, multi‐step dewetting strategy, creating wafer‐scale nanoclusters. This process strategically forms a robust many‐body system by introducing numerous small satellite nanoparticles between larger particles. Crucially, this design achieves a high collective enhancement that surpasses even optimized few‐body systems, despite having larger individual gaps. Under optimized conditions, these substrates exhibit a surface‐enhanced Raman scattering enhancement factor approaching 4 × 10^8 with unprecedented reproducibility (RSD of ∼10%). This scalable, low‐cost concept establishes a practical route toward reproducible wafer‐scale nanophotonic platforms for sensing, spectroscopy, and quantum technologies.

Sozial-emotionale Kompetenzen und kooperatives Lernen im diversitätssensiblen Mathematikunterricht. Posterpräsentation auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Hellmich, Frank; Grosche, M; Zimmer, L; Grüßing, M; Weß, N

Lehrkräfteperspektiven auf die Förderung sozial-emotionalen Lernens in der Grundschule. Posterpräsentation auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Funk, Michael; Hellmich, Frank

Vom Online-Kurs zur Präsenzfortbildung - Plicht, Katja; Burde, Jan-Philipp; Costan, Kasim; Gieshoff, Rike Isabel; Kulgemeyer, Christoph; Lässer, Armin; Riese, Josef; Schubatzky, Thomas; Weiler, David Christoph (Professionelles Handeln in einer Kultur der Digitalität: Ergebnisse aus dem Kompetenzzentrum MINT)
Im ComeMINT-Netzwerk wurde für das Fach Physik ein zweiphasiges Fortbildungskonzept zum Einsatz digitaler Medien im Physikunterricht entwickelt. Die erste Phase besteht aus einem Online-Selbstlernkurs auf der Plattform iMooX, welcher neben einer Einführung in das Lernen mit digitalen Medien auch Module zu spezifischen Medien wie z. B. Erklärvideos, digitale Messwerterfassung, Smartphones im Physikunterricht oder Mikrocontroller umfasst. Darauf aufbauend werden vertiefende Präsenzfortbildungen zu einzelnen Medien an den beteiligten Standorten angeboten, die einen stärkeren Praxisbezug verfolgen. Der Beitrag stellt neben den Konzepten des Online-Selbstlernkurses und den Präsenzfortbildungen auch die bisherigen Erfahrungen aus der Implementation der Fortbildung in die Praxis vor.
Keywords: Digitale Medien; Online-Kurs; Präsenzfortbildung; Physikunterricht

Staying with the Cracks: From Quick Fixes to Transformative Explainable AI - Menne, Anna Lena (6th International Conference on Anticipation: Book of Abstracts)

Holding Democracy Together: A common European baseline for trustworthy digital democracy in Europe (Policy Brief) - Rogowska, Gabriela; Domenici, Diego Dylan; Yilmaz, Fatih; Ceselli, Luca; Coenen, Laurien; Fuchs, Christian; Klinge, Xenia; Ruiz de Assin de los Santos, Maria

Die Widerruflichkeit der Verbraucherbürgschaft – a never ending story - Bartlitz, David; Hoffmann, Jochen (JuristenZeitung (JZ))

Limitations of entangled two-photon absorption detection - Pollmann, René; Roeder, Franz; Silberhorn, Christine; Brecht, Benjamin (Physical Review A)
We introduce a method for determining the sensitivity of any given entangled two-photon absorption (ETPA) measurement. By modeling all signal and noise contributions to the measurement, we derive a single numerical value that describes the sensitivity of the ETPA measurement in Göppert-Mayer units. This allows us to directly compare vastly different experimental approaches and determine whether ETPA will be detectable under the given conditions. Therefore we can quantify the effect of any change to a given experimental apparatus and identify the ideal optimization pathway.

Fast Distributed Computation of Compact Routing Schemes - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (Lecture Notes in Computer Science)

Supervised Distributed Computing: Efficiency and Robustness under a Majority of Adversarial Workers - Augustine, John; Hillebrandt, Henning; Kumar, Manish; Scheideler, Christian; Werthmann, Julian (Proceedings of the ACM Symposium on Principles of Distributed Computing)

Quantitative Modelling of Dynamic Nonlinearity in Piezoelectric Components - Friesen, Olga; Hölscher, Jonas; Spieker, Carsten; Förstner, Jens; Claes, Leander

A Soundness and Precision Benchmark for Java Debloating Tools - Klauke, Jonas; Ohlmer, Tom; Schott, Stefan; Ponta, Serena Elisa; Fischer, Wolfram; Bodden, Eric (Proceedings of the 2025 Workshop on Software Supply Chain Offensive Research and Ecosystem Defenses)
Modern software development reuses code by importing libraries as dependencies. Software projects typically include an average of 36 dependencies, with 80% being transitive, meaning they are dependencies of dependencies. Recent research indicates that only 24.9% of these dependencies are required at runtime, and even within those, many program constructs remain unused, adding unnecessary code to the project. This has led to the development of debloating tools that remove unnecessary dependencies and program constructs while balancing precision by eliminating unused constructs and soundness by preserving all required constructs. To systematically evaluate this trade-off, we developed Deblometer, a micro-benchmark consisting of 59 test cases designed to assess support for various Java language features in debloating tools. Each test case includes a manually curated ground truth specifying necessary and bloated classes, methods, and fields, enabling precise measurement of soundness and precision. Using Deblometer, we evaluated three popular Java debloating tools: Deptrim, JShrink, and ProGuard. Our evaluation reveals that all tools remove required program constructs, which results in changed semantics or execution crashes. In particular, the dynamic class loading feature introduces unsoundness in all evaluated tools. Our comparison shows that Deptrim retains more bloated constructs, while ProGuard removes more required constructs. JShrink’s soundness is significantly affected by limited support for annotations, which leads to corrupted debloated artifacts. These soundness issues highlight the need to improve debloating tools to ensure stable and reliable debloated software.

Wie funktionieren (Pseudo)wissenschaften? Ein Seminarkonzept für angehende Lehrkräfte naturwissenschaftlicher Fächer - Webersen, Yvonne; Riese, Josef (Demokratiebildung in der Lehrkräftebildung (Arbeitstitel). Paderborner Beiträge zur Bildungsforschung und Lehrkräftebildung.)

Wideband Frequency Synthesis Using Dual-Optical Phase-Locked Loop Synchronized to Optical Comb - Surendranath-Shroff, Vijayalakshmi; Bahmanian, Meysam; Scheytt, J. Christoph (2026 IEEE MTT-S Radio Frequency Systems and Applications Symposium (IMS RFSA))

Unpacking [Whose] Imaginary: Reflections from a Workshop on Digital Imaginaries - Menne, Anna Lena; Schulz, Christian

Soziales Lernen in der Grundschule - ein Praxisprojekt zur Entwicklung des PET - Paderborner Entwicklungstraining für Mensch und Tier. Ein Training zur Unterstützung der individuellen Entwicklung aller Beteiligten. - Mombeck, Mona; Caruso, Carina (Diskurse und Praktiken der Heterogenität. Pädagogisches Handeln in heterogenen Settings. Mit einem Fokus auf die Elementar- und Primarbildung)

Single-stage setting of blind rivet nuts without pre-drilling - Böhm, Yannic; Meschut, Gerson (Discover Mechanical Engineering)
Abstract The increasing use of thin-walled profiles in automotive battery housing construction is leading to a growing demand for one-sided access mechanical fasteners. Currently, the installation of blind rivet nuts still requires pre-drilling using chip-forming operations. In Meschut and Meyer (Vorlochfreies Setzen von Funktionselementen mittels Fließformen, Europäische Forschungsgesellschaft für Blechverarbeitung e.V. (EFB), Hannover, 2021), a chipless, two-step method for installing blind rivet nuts was developed, in which flow-drilling is the initial step. To eliminate the pre-drilling operation and optimise the joining process of blind rivet nuts, a pilot-hole-free joining method using a flow-drilling process is being pursued. The use of these blind rivet nuts can significantly simplify the joining process by eliminating chip-forming pre-drilling operations. Additionally, the screw-through capability reduces screw variance in automated fastening, optimising the feeding process by minimising the risk of incorrect screw selection. This work aims to develop a single-step process for the installation of a blind rivet nut. To achieve this, it is necessary to design the geometries of both the blind rivet nut and the flow-drill former, which also serves as the mandrel for the blind rivet nut. In addition to the geometries of the tools and functional elements, the flow-drilling process itself has been developed. Special attention is given to the pull-through and the formation of the closing head. To optimise the closing head formation, an iterative optimization process was used. The quality of the pull-through is improved by varying the tip geometries and adjusting the process parameters during flow-drilling.

Potenziale und Limitationen empirischer Forschung zu interreligiösen Lehr- und Lernprozessen in Schule und Hochschule - Meyer, Karlo; Caruso, Carina (Theo-Web)
Dieser Beitrag schließt an die anderen Artikel dieses Themenheftes an. Dabei werden mögliche Strukturen empirischer Forschung zu interreligiösen Lehr-Lernprozessen auf der Hochschulebene vorgeschlagen. Mögliche Zieloptionen, Ebenen und Fallstricke für die empirische Forschung zu interreligiösen Lehr-Lernprozessen werden diskutiert. Des Weiteren werden Erkenntnisse bisheriger Forschungsbemühungen zu interreligiösen Lehr-Lernprozessen zusammengefasst und ein strukturierter Ausblick auf Optionen empirischer Forschungen im universitären Bereich gegeben, wobei die vorangehenden Aufsätze dieses Themenheftes hinzugezogen werden.
Keywords: Interreligiöses Lernen; Lehr-Lernprozesse; Religionspädagogik; Hochschuldidaktik; empirische Forschung

Quantum speedup from nonclassical polarization - Aßbrock, Tim; Sperling, Jan; Ares, Laura (Physical Review Research)
We develop a framework for identifying nonclassical speedups in systems with polarization, likewise spin degrees of freedom. By confining the dynamics to the manifold of angular momentum coherent states, which act as the classical reference in this case, we compute the speed limit that bounds the rate of change of the state achievable without generating quantum coherence. A comparison with the unrestricted quantum speed limit enables the quantitative identification of speedups arising from polarization nonclassicality. We apply this framework to the cross-Kerr interaction, demonstrating a persistent speedup scaling as <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi mathvariant="script">O</a:mi> <a:mo>(</a:mo> <a:msqrt> <a:mi>N</a:mi> </a:msqrt> <a:mo>)</a:mo> </a:mrow> </a:math> with the photon number <c:math xmlns:c="http://www.w3.org/1998/Math/MathML"> <c:mi>N</c:mi> </c:math> , with a parity effect in favor of even photon numbers. The results establish polarization nonclassicality as a genuine dynamical resource, linking quantum coherence to quantum-enhanced evolution speeds in nonlinear photonic systems.

Generative Künstliche Intelligenz im Kontext von Lehren, Lernen und Beraten: Eine Perspektive der Pädagogischen Psychologie - Scheiter, Katharina; Bach, Katharina M.; Bauer, Elisabeth; Brod, Garvin; Bromme, Rainer; Buhl, Heike M.; Gagl, Benjamin; Greiff, Samuel; Hefter, Markus H.; Janke, Stefan; Lindner, Marlit A.; Mayweg, Elisabeth; et al. (Psychologische Rundschau)